Core concepts of accounting systems - Moscove, Stephen A.; Simkin, Mark G. ;Bagranoff, Nancy A. (Singapore : John Wiley & Son, Inc., 2001)
Every aspects of accounting has been fundamentally changed by information technology and internet. The advent of the information age affects financial accounting, managerial accounting, auditing and tax; in other words, the accounting profession in its entirely.
Part One. An Introduction to Accounting Information Systems -- Chapter 1. Accounting Information Systems and the Accountant -- Chapter 2. The Technology of Accounting Information System -- Chapter 3. Documenting Accounting Information System -- Part Two. Accounting Information Systems for Collecting, Recording and Storing Business Data -- Chapter 4. Transaction Processing: Fundamentals and Major Processing Cycles -- Chapter 5. Transaction Processing: Additional Cycles, Special Industries and Accounting Software -- Chapter 6. Databases and Data Modeling -- Part Three. Controls and Security in Accounting Information Systems -- Chapter 7. Introduction to Internal Control Systems --Chapter 8. Controls for Computerized Accounting Information Systems -- Chapter 9. Computer Crime and Ethics -- Chapter 10. Auditing Computerized Accounting Information System -- Part Four. Developing Effective Accounting Information System -- Chapter 11. Systems Study: Planning and Analysis --Chapter 12. Systems Study: System Design -- Chapter 13. Systems Study: Implementations and Maintenance -- Part Five. Special Topics in Accounting Information Systems -- Chapter 14. Information and Knowledge Processing Systems in Accounting -- Chapter 15. Electronic Commerce and the Internet.
Includes index.
Keywords: ACCOUNTING INFORMATION SYSTEMS